2015
DOI: 10.1002/ange.201410618
|View full text |Cite
|
Sign up to set email alerts
|

Elektronentransfer in Peptiden: Bildung von Silbernanopartikeln

Abstract: Einige Mikroorganismen zeigen anaerobe mineralische Respiration, bei der sie Metallionen zu Metallnanopartikeln reduzieren. Hierbei werden Peptide als Medium für den Elektronentransfer (ET) verwendet. Diese Reaktionsklasse wird anhand eines Modellpeptids und Silber als Metall diskutiert. Erstaunlicherweise können Silberionen, die von Peptiden mit Histidin als silberbindender Aminosäure und Tyrosin als photoinduziertem Elektronendonor gebunden sind, nicht unter ET‐Bedingungen zu Ag‐Nanopartikeln (AgNPs) reduzie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Such peptides can be designed to conform to specific secondary structures, such as helices and β-strands, to allow the dynamics and kinetics of electron transfer to be studied in a more controlled environment. 3,4 In addition, they can be specifically functionalized along their backbone to enable precision-branching, analogous to three-dimensional molecular circuitry. 5 While molecular electronics provides an opportunity to begin to redefine integrated circuit technologies, 6 one must first understand and subsequently be able to predict and control the associated charge transfer dynamics and mechanisms before this vision can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Such peptides can be designed to conform to specific secondary structures, such as helices and β-strands, to allow the dynamics and kinetics of electron transfer to be studied in a more controlled environment. 3,4 In addition, they can be specifically functionalized along their backbone to enable precision-branching, analogous to three-dimensional molecular circuitry. 5 While molecular electronics provides an opportunity to begin to redefine integrated circuit technologies, 6 one must first understand and subsequently be able to predict and control the associated charge transfer dynamics and mechanisms before this vision can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this hypothesis, follow‐up studies used tetrapeptides His‐X‐Y‐Tyr (1) and His‐X‐Y‐Phe (2), replacing tyrosine with phenylalanine, and where X and Y are Pro and Aib, respectively, were synthesized (Figure 4b and ref. [122]). NMR‐titrations showed that the silver ion binds in a first step to histidine as confirmed by single‐crystal X‐ray diffraction.…”
Section: Mechanisms Of Microbial Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Then, the initially formed AgNPs, based on chemical reduction, serve as nucleation points for the further and rapid addition of atoms from the light‐induced reduction. [ 122 ] Thus, a synergic mechanism combining the chemical and the light‐induced reduction of silver ions should be considered, taking into consideration the experimental conditions. Indeed, due to the variation in the composition of the growth media and buffer solutions in which the experiments are being carried out, reducing molecules may be present.…”
Section: Mechanisms Of Microbial Synthesis Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation